In vitro fermentation of novel microwave-synthesized non-digestible oligosaccharides and their impact on the composition and metabolites of human gut microbiota. (April 2019) - Wang, Haisong; Ren, Pengfei; Mang, Lai; Shen, Nan; Chen, Jinran; Zhang, Yiwen
Graphical abstract: Highlights: Impact of novel oligosaccharides on gut microbiota and its metabolites were studied. Significant stimulation of specific bacteria in response to particular oligosaccharides. Polydextrose and polygalactose exhibit prebiotic potential activities. Polygalactose produced the largest amount of SCFAs than polydextrose and polymannose. Abstract: Three microwave-synthesized non-digestible oligosaccharides (polydextrose, polygalactose and polymannose) were fermented using an in vitro pH-controlled batch incubation inoculated with human fecal slurries, simulating the events in the distal colon. Microbial changes and short-chain fatty acids (SCFAs) were analyzed using 16S rRNA gene sequencing and gas chromatography, respectively. Polydextrose and polygalactose significantly ( P  < 0.05) stimulated the growth of Bifidobacterium suggesting prebiotic potential activities. Besides, polygalactose increased the abundance of the Lactobacillus, while polymannose remarkably ( P  < 0.05) stimulated the growth of Erysipelotrichaceae . Our results also revealed that the fermentation of polygalactose by gut microbiota produced the largest amount of SCFAs which was dominated by the acetate and propionate as compared to polydextrose and polymannose. In addition, more butyrate was produced from polydextrose. These results suggest that microwave-synthesized polydextrose, polygalactose, and polymannose are potential promising non-digestible oligosaccharides in modulating human gut microbiota.